Ewing Sarcoma of Ovary-An Unusual Presentation (Global Journal of Medical Research, 2016)
Ewing's sarcoma generally arises from bones and soft tissues. Primitive neuroectodermal tumor (PNET) and Ewing sarcoma constitute Ewing family of tumors. In International literature there have been rare reports of Ewing's sarcoma as either primary tumor of ovary or as metastatic disease involving ovary. No such case has yet been reported in Pakistan. Here a case is being presented who was diagnosed as Ewing's sarcoma of ovary. Workup showed no involvement of the bones.
Keywords: ewing#x2019; s sarcoma; PNET; ovary